nutritional composition and in vitro digestibility of indigofera sp at different interval and intensity of defoliations - Tarigan, Andi; Abdullah, L; Ginting, S.P; Permana, I.G (Indonesian Journal of Animal and Veterinary Sciences, 2010)
One of the main constraints in increasing livestock productivity in the tropical region is the scarcity of good quality feed throught the year, particularly during the long-dry season. Being a leguminous tree, Indigofera sp known to be tolerant to dry climate and salinity, should be considered as alternative fodder for ruminant animals. This study is aimed to investigate the productivity and some nutritional quality of Indigofera sp under different interval and hight of defoliation. The experiment was designed in a randomized block of factorial treatments. The factors were interval of defoliation (30, 60 and 90 days) and hight of defoliation (0.5, 1.0 and 1.5 m above ground level). Indigofera sp was planted in 4 x 3 m plots of 36 plots (4 replications) and were harvested at 8 months old. The DM production, chemical composition and in vitro digestibility were measured according to the treatments. The highest DM productivity was (33.25 t ha-1 y-1) at defoliation interval of 90 days and defoliation hight of 1.5 m, and was not different (P > 0.05) from the treatment combination of 60 days defoliation interval and 1,5 m defoliation hight (31.23 t ha-1 y-1). The highest leaf/stem ratio was 2.6 (P < 0.05) in the 30 day defoliation interval across the defoliation hight. The OM content of Indigofera sp was not affected by defoliation treatments and ranging from 884.6 to 906.8 g/kg. The highest NDF and ADF contents were (P < 0.05) in the 90-d defoliation interval and 1.0 m (387.9 and 272.6 g/kg, respectively) and were not different (P > 0.05) for the 90-d defoliation interval and 1.5 m defoliation hight (385.6 and 267.0 g/kg, respectively). The crude protein content was lowest (P < 0.05) in the 30-d defoliation interval across the defoliation hight ranging from 211.2 to 219.7 g/kg, and it was not different between the 60 and 90-d defoliation interval across the defoliation hight (255.0-258.1 g/kg and 230.3-236.0 g/kg, respectively). Defoliation hight did not affect (P > 0.05) the DM and OM in vitro digestibility. They were at the 90-d defoliation interval ranging from 680.2 to 706.8 g/kg and from 668.6 to 686.8 g/kg, respectively across the defoliation hight different. The DM and OM digestibility were not different (P > 0.05) between the 30 and 60-day defoliation intervals. It is concluded that when planted at low land of wet climate the combination of a 60-d defoliation interval and 1.5 m defoliation hight is an optimum cutting management in utilization of Indigofera sp as foliage for ruminant. Key Words: Defoliation, Nutritive Quality, Productivity, Indigofera sp